The influence of perception, motivation, and taxation knowledge on career choice in the field of taxation (empirical study of economics students in Pringsewu Regency) - Izzatti Nur Hasanah; Andi Mulyono; Fauzan Fuadi; Fitria Fertha Agustina (Indonesia Accounting Research Journal, 2025)
A profession in taxation offers large opportunities due to the increasing demand for tax professionals consistent with the developing complexity of tax structures and rules. but, student interest in pursuing a career in taxation stays low, in large part because of a lack of understanding approximately career opportunities on this subject. this is evidenced through findings at Andalas college, which display that the lack of awareness amongst college students about the taxation zone and its profession possibilities is a first-rate issue contributing to their low hobby in taxation careers. This have a look at ambitions to study the affect of perception, motivation, and taxation knowledge on the career preference within the taxation discipline amongst college students of Economics school in Pringsewu Regency. The take a look at employs a quantitative method with a move-sectional method. The pattern become decided on the use of comfort sampling, with number one information accumulated thru a Likert-scale questionnaire allotted via Google paperwork to fifty five college students. facts have been analyzed the use of multiple linear regression with SPSS version 25.0. The outcomes indicate that belief notably impacts profession desire in taxation. Likewise, motivation and taxation expertise actually have a substantial effect on college students’ profession choice in this field.